Comparison of neurogenic lower urinary tract dysfunctions in open versus closed spinal dysraphism: A prospective cross‐sectional study of 318 patients. Issue 8 (2nd August 2018) - Peyronnet, Benoit; Brochard, Charlène; Jezequel, Magali; Hascoet, Juliette; Alimi, Quentin; Senal, Nelly; Carsin‐Nicole, Béatrice; Riffaud, Laurent; Le Reste, Pierre‐Jean; Bonan, Isabelle; Olivari‐Philiponnet, Camille; Siproudhis, Laurent; et al.
Abstract : Aims: To compare the neurogenic lower urinary tract dysfunction (NLUTD) in patients with closed spinal dysraphism (CSD) versus patients with open spinal dysraphism (OSD) as well as their management patterns. Methods: A prospective cross‐sectional study was conducted between September 2007 and December 2015 including all spina bifida patients seen at the multidisciplinary French national referral center for spina bifida. NLUTD and its management were compared between the OSD and CSD groups. Results: Three hundred and eighteen patients were included for analysis: 100 with a CSD (31.5%) and 218 with an OSD (68.6%). The prevalence of urinary incontinence did not differ significantly between the two groups (43% vs 52.8%; P = 0.11), the mean Qualiveen score was also similar (2.7 vs 2.5, P = 0.22). The voiding mechanism was clean intermittent catheterization, spontaneous voiding, suprapubic tube, and ileal conduit in 55% versus 44%; 29.8% versus 47%; 2.8% versus 3% and 11.9% versus 6% of OSD and CSD patients, respectively ( P = 0.02). There were comparable prevalences of detrusor overactivity (36.5% vs 38.8%; P = 0.68) and impaired bladder compliance (34.9% vs 31.7%; P = 0.56) in both groups. Augmentation cystoplasty was more common in patients with OSD (32.1% vs 11%; P < 0.0001). Conclusions: In this prospective cohort, NLUTD were more common in OSD with a higher rate of patients requiring a surgical treatment and a lower rate of patients with preserved spontaneous voiding. However, when present, NLUTD was as severe and troublesome in patients with closed versus open spinal dysraphism.